FULL CALL AUCTION AND MARKET LIQUIDITY: LESSONS FROM IDX - Teto, Columbanus; Husodo, Zaäfri Ananto (UI Scholars Hub, 2025)
Background: This study investigates the impact of the Full Call Auction mechanism implemented by the Indonesia Stock Exchange in 2024 on stocks listed under the Special Monitoring Board. The research aims to evaluate how the FCA affects market liquidity, particularly bid-ask spreads and trading volume, within the financial sector stocks. Methods: Employing a heterogeneous Difference-in-Differences approach, the analysis compares stock-level liquidity indicators before and after the FCA implementation. Findings: While overall treatment effects appear statistically insignificant, subgroup analysis reveals that stocks with longer exposure to the FCA exhibit significantly wider bid-ask spread and persistent reductions in trading volume. These findings indicate that, although the FCA was introduced to improve transparency and market integrity, it may have inadvertently reduced market participation and liquidity. Conclusion: The study highlights the critical role of market design in emerging markets and recommends adopting complementary mechanisms, such as Designated Market Makers, to support liquidity in auction-based systems. Novelty/Originality of this article: This research contributes to the market microstructure literature and provides practical insights for regulators seeking to enhance trading efficiency in emerging capital markets.